Beyond the Balance Sheet: Understanding Labor Market Dynamics Following Accounting Fraud - Tanti Sugiharti; Mohammad Chaidir (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review examines the labor market dynamics following accounting fraud, highlighting the significant impact of corporate misconduct on employee outcomes. Through a synthesis of existing studies, the review identifies key consequences for employees at fraudulent firms, including substantial wage losses, increased turnover rates, and overall job instability. The analysis reveals that, despite initial employment growth during fraud periods, employees ultimately face negative repercussions as firms unwind overexpansion once fraudulent activities are exposed. The review also emphasizes the disproportionate effects on lower-wage employees and those in thin labor markets, underscoring the need for targeted interventions. Additionally, the findings call for enhanced corporate governance and regulatory frameworks to protect employee interests and foster ethical business practices. This research not only contributes to the understanding of the repercussions of accounting fraud on labor market dynamics but also serves as a critical reminder of the interconnectedness of corporate behavior and employee welfare.